Analysis of Green Hotel Implementation at Holiday Inn Jakarta Kemayoran - Julita, Julita; Basri, Goh Andy; Anastasia, Melvin (International Journal of Green Tourism Research and Applications, 2024)
The tourism industry often overlooked environmental vulnerability, especially its contribution to climate change, necessitating attention. Hotels, a key tourism sector, significantly impact the environment, emitting substantial carbon dioxide and consuming large amounts of water. The Indonesian Ministry of Tourism emphasizes eco-friendly hotel management through the Green Hotel program. This research, a comprehensive investigation, employs qualitative methods, including documentation review, observation, and interviews with hotel personnel, including the General Manager, Chief Engineer, Business Development Executive, and Housekeeping Manager. The study explores Green Hotel practices at Holiday Inn Jakarta Kemayoran, part of IHG. The data analysis, involving data collection, data reduction, data display, and concluding/verifying data, is robust and thorough. It shows that the effective implementation of Green Engage at the hotel, IHG's sustainability program, is evident in eco-friendly materials, energy efficiency, water conservation, and waste management. These efforts contribute to environmental conservation and reduce costs, emissions, and waste while increasing occupancy rates, reflecting guest preference for green accommodations. This research underscores the positive impact of Green Hotel implementation on both the hotel's performance and environmental conservation, instilling hope for a more sustainable future. Continuous efforts are needed to enhance sustainability practices, embracing more eco-friendly initiatives and involving guests in environmentally conscious actions.